Cerebrospinal Fluid Biomarkers Are Associated With Glial Fibrillary Acidic Protein and αII-spectrin Breakdown Products in Brain Tissues Following Penetrating Ballistic-Like Brain Injury in Rats - DeDominicis, Kristen E.; Hwang, Hye; Cartagena, Casandra M.; Shear, Deborah A.; Boutté, Angela M. (Frontiers in Neurology, 2018)
Treatments to improve outcomes following severe traumatic brain injury (TBI) are limited but may benefit from understanding subacute-chronic brain protein profiles and identifying biomarkers suitable for use in this time. Acute alterations in the well-known TBI biomarkers glial fibrillary acidic protein (GFAP), αII-spectrin, and their breakdown products (BDPs) have been well established, but little is known about the subacute-chronic post-injury profiles of these biomarkers. Thus, the current study was designed to determine the extended profile of these TBI-specific biomarkers both in brain tissue and cerebral spinal fluid (CSF). Protein abundance was evaluated in brain tissue samples taken from regions of interest and in CSF at 24 hours, 3 days, 7 days, 1 month, and 3 months following severe TBI in rats. Results showed increased full length GFAP (GFAP-FL) and GFAP-BDPs starting at 24 hours that remained significantly elevated in most brain regions out to 3 months post-injury. However, in CSF, neither GFAP-FL nor GFAP-BDPs were elevated as a consequence of injury. Regional-specific reduction in αII-spectrin were evident in brain tissue samples from 24 hours through 3 months. In contrast, SBDP-145/150 was robustly elevated in most brain regions and in CSF from 24 hours through 7 days. Correlation analyses revealed numerous significant relationships between proteins in CSF and brain tissue or neurological deficits. This work indicates that TBI results in chronic changes in brain protein levels of well-known TBI biomarkers GFAP, αII-spectrin, and their BDPs and that SBDP-145/150 may have utility as an acute-chronic biomarker.